Studi Kelayakan Pendirian Industri Ekstraksi Emas dari E-waste di Surabaya - Budijono, Zefanya; Ronyastra, I Made; Soegiharto, Stefanus (Keluwih: Jurnal Sains dan Teknologi, 2021)
Abstract-- In this modern era along with the development of technology can not be separated from the waste produced. Waste from solid from technological development is electronic waste or often called e-waste. Along with the development of technology followed by an increase in e-waste in both developed and developing countries. E-waste itself is composed of a variety of substances from heavy metals to chemicals and even precious metal groups also make up the e-waste itself. It is said e-waste because it has not been used either because the technology has been left behind by the times, its performance has declined, or it cannot be used. Even so the constituent content in e-waste does not lose its value, one of which is precious metals that can be recycled. In this research, the opportunity to look at the use of precious metal content that is still valuable and can be taken from e- waste is gold, taking into account existing market share and methods for taking gold content in e-waste. This gold extraction activity from e-waste is more commonly known as urban mining outside Indonesia, because from the observations of researchers in Indonesia, especially in Surabaya, this business activity is still rarely an additional reason to conduct a feasibility study for the establishment of this industry in Surabaya. With the characteristics of the City of Surabaya it is assumed to supply qualifie d raw materials for processing, besides that Surabaya is also one of the large market shares in Indonesia. In this research the method of extracting raw materials used is hydrometallurgy, because the product produced is gold so special security management was formed. In addition, because both raw materials and supporting materials in production are classified as B3, special management is also carried out related to waste treatment and worker safety in operational activities. At the founding of this industry capital came from bank loans and own capital with a ratio of 33:67 for a total project cost of Rp 1,455,738,638. The IRR calculation results in this industry are greater than MARR that is 361%> 10.48%), for the NPV value obtained Rp 6,223,244,133.67, then with a 5 -year planning horizon only requires a DPP of 0.313891047 or about 3 months ( smaller than the planning horizon for 5 years). For the sensitivity analysis the most important variables are the selling price and the cost of raw materials.Keywords: e-waste, hydrometallurgy, industrial planning, feasibility study, urban mining Abstrak -- Pada era modern ini seiring perkembangan teknologi tidak lepas dari limbah yang dihasilkan. Limbah dari padat dari perkembangan teknologi adalah sampah elektronik atau yang sering disebut e-waste. Seiring perkembangan teknologi diikuti peningkatan e-waste baik di negara maju maupun negara berkembang. E-waste itu sendiri tersusun dari berbagai zat baik logam berat hingga zat kimia bahkan golongan logam mulia juga menjadi penyusun dari e-waste itu sendiri. Dikatakan e-waste karena sudah tidak digunakan baik karena teknologi tersebut sudah tertinggal oleh jaman, kinerjanya menurun, maupun sudah tidak dapat digunakan. Walaupun begitu kandungan penyusun pada e-waste tidak kehilangan nilainya salah satunya logam mulia yang dapat didaur ulang. Pada penelitian ini melihat peluang pemanfaatan kandungan logam mulia yang masih bernilai dan dapat diambil dari e-waste yang ada yaitu emas, dengan mempertimbangkan pangsa pasar yang ada serta metode dalam mengambil kandungan emas pada e-waste. Kegiatan mengekstraksi emas dari e-waste ini lebih sering dikenal dengan urban mining di luar Indonesia, karena dari pengamatan peneliti di Indonesia terutama di Surabaya kegiatan bisnis ini masih jarang me njadi tambahan alasan untuk melakukan penelitian studi kelayak pendirian industri ini di Surabaya. Dengan karakteristik Kota Surabaya diasumsikan pasokkan bahan baku mumpuni untuk diolah, selain itu Surabaya juga salah satu pangsa pasar yang besar di Indonesia. Pada penelitian ini metode pengekstraksian bahan baku yang digunakan adalah hidrometalurgi, karena produk yang dihasilkan adalah emas maka dibentuk manajemen keamanan khusus. Selain itu karena baik bahan baku dan bahan pendukung dalam produksi tergolong B3 maka juga dilakukan manajemen khusus terkait pengolahan limbah serta keselamatan pekerja pada kegiatan operasional. Pada pendirian industri ini modal berasal dari pinjaman bank dan modal sendiri dengan rasio 33:67 untuk total project cost sebesar Rp 1.455.738.638. Hasil perhitungan IRR pada industri ini bernilai lebih besar dari MARR yaitu 361% > 10,48%), untuk nilai NPV didapatkan Rp 6.223.244.133,67, maka dengan horizon perencanaan 5 tahun hanya memerlukan DPP sebesar 0,313891047 atau sekitar 3 bulan (lebih kecil dibandingkan horizon perencanaan selama 5 tahun). Untuk analisis sensitivitas variabel yang peling berpengaruh adalah harga jual dan biaya bahan baku.Kata Kunci: e-waste , hidrometalurgi, perencanaan industri, studi kelayakan, urban mining